Zinc Supplementation For Respiratory Illness And Acute Gastroenteritis As Complement Treatment For Covid-19 - Chandrika Murugaiah; Constance Liew Sat Lin; Hassanain Al-Talib; Mehru Nisha; Tunung Robin; Tuan Zainazor Tuan Chilek; Atif Amin Baig; Rhanye Mac Guad; May Zaw Soe; ABM Tofazzal Hossain; Falah Abbas Mohamad Salih; Mustafa al Shagga (NLM (National Library of Medicine, 2020)
An outbreak of atypical pneumonia by the novel coronavirus disease 2019 (COVID-19), has been reported in Wuhan, China since December, 2019. It is a severe respiratory illness with many other symptoms such as gastroenteritis. Clinical trials has proved that Zn is a promising supplement that can ease of cough, fever and vomiting, dysentery, respiratory illness, diarrhea duration and recovery, duration of hospitalization and morbidity. This article suggests a potential role, which should be considered in the clinical management, and safeness for Zn supplementation for respiratory illness and acute gastroenteritis as compliment treatment for covid-19.